Use of Anatomage Virtual Dissection table for Teaching Anatomy in Medical College - Fauzia Qureshi, Uzma Waseem, Raafea Tafweez, Syeda Zakia, Sibgha Fatima, Fariha Qureshi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Conventional teaching methodology for subject of Anatomy by use of cadaver is becoming obsolete because of unavailability of cadaver to the medical institutes. Anatomy is an important subject in basic medical sciences, thus need to be taught in depth in early year of medical curriculum. As availability of cadavers for teaching Anatomy has become extremely difficult. Aim: To evaluate students’ opinion on the use of the Anatomage 3 D virtual dissection table as an additional teaching tool to cadaver dissection in studying anatomy and understanding the relations of structures. Methods: A descriptive retrospective study was held at the department of Anatomy Azra Naheed Medical College. An electronic questionnaire was given to 2nd year MBBS students in which 6 questions regarding opinion of students who were taught through cadaveric specimen & 3D Anatomage table, regarding use of 3D Anatomage for active learning of anatomy topics. Results: Present study showed that the most of the students preferred using 3D Anatomage for learning anatomy as it enhances active learning. 80.4% responded positively in developing deeper understanding of the topic with use of Anatomage table as compared to conventional teaching. 89.5% responded positively to visualize better the anatomical features of different parts of body with the help of anatomage table. 81.7% responded positively regarding use of Anatomage table in active learning and in developing interest in subject of Anatomy. Conclusion: Students consider the use of the anatomage table, an effective teaching tool for gross anatomy, for visualizing anatomical relation of different parts of the body, for deeper understanding and active learning of Anatomical features, and in developing interest in the subject of Anatomy. Students can incorporate digital anatomy into the learning and teaching of basic medical science. The use of 3DAnatomage table gives the impression to have an important role in Medical education Keywords: Anatomage Virtual dissection table, Traditional dissection, Learning anatomy, 3D interactive anatomage table